2003
DOI: 10.1051/0004-6361:20030665
|View full text |Cite
|
Sign up to set email alerts
|

Numerical tests of dynamical friction in gravitational inhomogeneous systems

Abstract: Abstract. In this paper,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…It is, however, still unclear how the inhomogeneity of the system distribution affects the satellite dynamics. Whereas Del Popolo (2003), Del Popolo & Gambera (1998) and Maoz (1993) show that dynamical friction increases the steeper the density profile is, Just & Peñarrubia (2002), following the theoretical scheme proposed by Binney (1977), hereinafter B77, find a negligible effect on the satellite orbit due to the symmetry of the inhomogeneous terms of dynamical friction.…”
Section: Introductionmentioning
confidence: 98%
“…It is, however, still unclear how the inhomogeneity of the system distribution affects the satellite dynamics. Whereas Del Popolo (2003), Del Popolo & Gambera (1998) and Maoz (1993) show that dynamical friction increases the steeper the density profile is, Just & Peñarrubia (2002), following the theoretical scheme proposed by Binney (1977), hereinafter B77, find a negligible effect on the satellite orbit due to the symmetry of the inhomogeneous terms of dynamical friction.…”
Section: Introductionmentioning
confidence: 98%
“…Maoz (1993) and follow-up papers (Sánchez-Salcedo 1999;Dominguez-Teneiro & Gómez-Flechoso 1998) used the fluctuation-dissipation theory with approximations similar to those presented here to derive the energy loss due to dynamical friction. Del Popolo &Gambera (1999) andDel Popolo (2003) compute the corrections due to a density enhancement spherically symmetric with respect to the massive body, which may be used to estimate the shielding effect on the friction force.…”
Section: Introductionmentioning
confidence: 99%
“…Chandrasekhar & von Neumann (1943) attempted to derive this force from a purely stochastic formalism in the case where the system is infinite and homogeneous and the stars have a Maxwellian velocity distribution. Their calculations were extended by Del Popolo & Gambera (1999); Del Popolo (2003) to an inhomogeneous medium with a density decaying as ρ ∼ r −p , assuming again that the velocity distribution of the stars is Maxwellian. In order to treat in a self-consistent manner more general situations of spatial inhomogeneity, and take into account collective effects, the formalism developed in the present paper is necessary.…”
Section: D3 An Ilustration Of Dynamical Friction In a Mestel Discmentioning
confidence: 99%
“…Kandrup (1983); Bekenstein & Maoz (1992); Maoz (1993); Nelson & Tremaine (1999); Chavanis (2008) reconsidered the interaction of a test particle with a background stochastic force in the context of the fluctuation-dissipation theorem, and showed that the friction force depends on the global structure of the system. This was also investigated in Del Popolo & Gambera (1999); Del Popolo (2003) which extended Chandrasekhar & von Neumann (1943)'s analysis to the case where the background particles are inhomogeneously distributed with a density profile decaying as ρ ∼ r −p . Kinetic theories for spatially inhomogeneous systems were developed in Severne & Haggerty (1976); Parisot & Severne (1979); Kandrup (1981); Chavanis (2008Chavanis ( , 2013 using position-velocity variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation